PENGARUH POC AIR LIMBAH BUDIDAYA IKAN LELE DAN DOSIS NPK TERHADAP SERAPAN HARA N DAN PERTUMBUHAN TANAMAN CABAI RAWIT (Capsicum frustescens L.) - Muthi, Ornela; Hermiyanto, Bambang; Ratnasari, Tri; Wijayanto, Yagus (Institute of Computer Science (IOCS), 2025)
The excessive use of inorganic fertilizers in the cultivation of bird’s eye chili (Capsicum frutescens L.) can lead to land degradation and reduced soil fertility, resulting in suboptimal plant growth and yield. One promising solution to address this issue is the utilization of catfish aquaculture wastewater as a raw material for liquid organic fertilizer (LOF). The nutrient content in catfish wastewater, such as nitrogen (N), phosphorus (P), and potassium (K), supports plant development. This study aimed to determine the effect of the combination of LOF from catfish wastewater and various NPK fertilizer doses on nitrogen uptake and the growth of bird’s eye chili plants. The research was conducted at the Greenhouse of the Agrotechnopark, University of Jember, from December 2024 to March 2025, using a factorial completely randomized design (CRD) with two factors: LOF type (no LOF, fresh LOF, and fermented LOF) and NPK dosage (10 g, 15 g, and 20 g per plant). Data were analyzed using ANOVA and further tested with DMRT at a 5% significance level. The results showed that the combination of fermented liquid organic fertilizer (POC) application and NPK dosage of 15 g per plant (or 300 kg/ha), which significantly affected the variables of plant height, number of leaves, number of branches, and root dry weight. It can be concluded that the utilization of catfish aquaculture wastewater as a liquid organic fertilizer, combined with a 25% reduction in NPK fertilizer dosage, can promote plant growth.